Evaluación Técnico Financiera de la mejor opción de cañoneo en los campos de la Gerencia de Operaciones y Desarrollo Apiay (GDA) de Ecopetrol S.A. (2020)
One of the most difficult problems to face today by the Oil Industry is the low productivity of the wells, which depends on several factors, one of the most important being the cannoning process. Gunship operations are fundamental and decisive in the production of the well from the stage of completion to the implementation of workover jobs. For this reason, the right selection of these operations should minimize future repairs and maximize the life of the well. This selection not only affects the production but also the maintenance of the well, which is reflected in the costs and operating times. In this way, the objective of this work is the evaluation of the cannon operations carried out in the fields of the Regional Vice-presidency Orinoquia (VRO), located in the Eastern Plains Basin, one of the most productive in the country; which will allow to determine the best technical operation as economically applied. For this purpose, the analysis was carried out based on the criterion of Productivity Index per foot shot and mD of permeability (IP / k * h), accompanied by the main petrophysics data and parameters for the correct practice of the process, which allowed determining the performance of the cannon operations carried out in the regional. The analysis was carried out in the Excel program in which a matrix was developed using a database, dynamic tables and graphs for the evaluation of operations.